Characterisation and comparison of adipose tissue macrophages from human subcutaneous, visceral and perivascular adipose tissue - Kralova Lesna, Ivana; Kralova, Anna; Cejkova, Sona; Fronek, Jiri; Petras, Marek; Sekerkova, Alena; Thieme, Filip; Janousek, Libor; Poledne, Rudolf (Journal of translational medicine, 2016)
BACKGROUND AND AIMS: Macrophages play important roles in adipose tissue inflammation and its consequences. Unfortunately, a detailed description of the macrophage phenotypes in different human adipose tissues is not available. SUBJECTS AND METHODS: Subcutaneous, visceral and perivascular adipose tissues were obtained from 52 living kidney donors during live donor nephrectomy. Stromal vascular fractions were isolated, and the macrophage phenotypes were analyzed by flow cytometry using surface markers (CD14, CD16, CD36, and CD163). RESULTS: In addition to CD16 positivity, pro-inflammatory macrophages also display high scavenger receptor CD36 expression. The great majority of CD16 negative macrophages express the anti-inflammatory CD163 marker. The presence of pro-inflammatory macrophages was almost twice as high in visceral (p < 0.0001) and perivascular (p < 0.0001) adipose tissues than in subcutaneous tissue. This difference was substantially more pronounced in the postmenopausal women subgroup, consequentlly, the total difference was driven by this subgroup. CONCLUSION: We obtained detailed information about M1 and M2 macrophage phenotypes in human adipose tissue. The visceral and perivascular adipose tissues had substantially higher pro-inflammatory characteristics than the subcutaneous tissue. The higher proportion of pro-inflammatory macrophages in the visceral adipose tissue of postmenopausal women might be related to an increased cardiovascular risk.
Keywords: Menopause; průtoková cytometrie; Inflammation; Subcutaneous Fat; Tissue Donors; dárci tkání; nitrobřišní tuk; separace buněk; podkožní tuk; Middle Aged; mužské pohlaví; fenotyp; Cell Separation; Flow Cytometry; Adipose tissue; Macrophages; Phenotype; ženské pohlaví; Humans; Intra-Abdominal Fat; lidé středního věku; makrofágy; Female; lidé; Male